Severe symptomatic hypocalcemia with probable transient parathyroid dysfunction following radioiodine therapy for Graves’ disease: a case report - Anamarija Jankulovska; Natasha Stojanoska; Tanja Makazlieva; Nevena Manevska; Sinisha Stojanoski (Oxford Medical Case Reports, 2026)
Abstract Background Radioactive iodine therapy (RAIT) is a definitive treatment for hyperthyroidism, but parathyroid effects are often underrecognized. Case Presentation A 66-year-old woman with a 30-year history of Graves’ disease underwent RAIT (555 MBq 131I) after long-term treatment with thiamazole and briefly with propylthiouracil without achieving remission. Two weeks after RAIT, she developed paresthesia and muscle cramps, progressing to hospitalization one week later with positive Chvostek’s and Trousseau’s signs. Laboratory tests showed severe hypocalcemia (ionized calcium 0.70 mmol/L), vitamin D deficiency, and low parathyroid hormone levels, consistent with parathyroid dysfunction (CTCAE Grade 3 hypocalcemia). She required intravenous and oral calcium plus vitamin D, with gradual improvement. At 9-month follow-up, calcium levels remained stable on supplementation, suggesting prolonged recovery of parathyroid function. She later developed post-RAIT hypothyroidism. Conclusion This case highlights the importance of considering transient parathyroid dysfunction in patients with symptomatic hypocalcemia after RAIT and supports long-term biochemical monitoring and supplementation.